2017
DOI: 10.1093/icesjms/fsx092
|View full text |Cite
|
Sign up to set email alerts
|

Inferring the annual, seasonal, and spatial distributions of marine species from complementary research and commercial vessels’ catch rates

Abstract: The objective of this study is to analyse at fine scale the annual, seasonal and spatial distributions of several species in the Eastern English Channel (EEC). On the one hand, data obtained from scientific surveys are not available all year through, but are considered to provide consistent yearly and spatially resolved abundance indices. On the other hand, on-board commercial data do cover the whole year, but generally provide a biased perception of stock abundance. The combination of scientific and commercia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 43 publications
0
29
0
Order By: Relevance
“…To reduce counting false zeros, both landed and discarded individuals that were sampled were considered. To reduce zero inflation, spatio-temporal biases and presence over estimations, only gear types with an even spatio-temporal coverage (set gillnet, trammel net, otter beam trawl and otter twin trawl and Danish seine net for Raja clavata), and a skate bycatch of more than one percent of the total hauls were analysed, similar to Bourdaud et al, (2017). Data outside the known ranges of skate depth distributions (accessed from ObsMer and SBTS data, >100 m for R. undulata and >150 m for R. clavata and R. montagui) and ICES divisions in which almost no skates were identified within were removed to reduce zero inflation ( Table 2).…”
Section: Predictor Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…To reduce counting false zeros, both landed and discarded individuals that were sampled were considered. To reduce zero inflation, spatio-temporal biases and presence over estimations, only gear types with an even spatio-temporal coverage (set gillnet, trammel net, otter beam trawl and otter twin trawl and Danish seine net for Raja clavata), and a skate bycatch of more than one percent of the total hauls were analysed, similar to Bourdaud et al, (2017). Data outside the known ranges of skate depth distributions (accessed from ObsMer and SBTS data, >100 m for R. undulata and >150 m for R. clavata and R. montagui) and ICES divisions in which almost no skates were identified within were removed to reduce zero inflation ( Table 2).…”
Section: Predictor Variablesmentioning
confidence: 99%
“…Fisheries-dependent and independent data comparative studies (e.g. Bourdaud et al, 2017 andPennino et al, 2016), have shown that distribution models using such data are complementary and coherent to independent models.…”
Section: Use Of Fisheries-dependent Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Scientific survey data usually have a broader and more homogeneous geographical coverage than commercial fishery data, as fishers target certain species and areas. However, scientific survey data have less intensity and temporal coverage (Pennino et al 2016;Bourdaud et al 2017). While both commercial and scientific data are important sources of information, it is a challenge to link the two types of data and provide a coherent picture (Poos et al 2013;Bourdaud et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, scientific survey data have less intensity and temporal coverage (Pennino et al 2016;Bourdaud et al 2017). While both commercial and scientific data are important sources of information, it is a challenge to link the two types of data and provide a coherent picture (Poos et al 2013;Bourdaud et al 2017). Currently, integrated commercial datasets rely on coupling data from logbooks, sales slips and the Vessel Monitoring System (VMS) to allocate landings to vessels' hauls and fishing grounds (Hintzen et al 2012).…”
Section: Introductionmentioning
confidence: 99%